Effects of the liposomal co-encapsulation of antigen and PO-CpG oligonucleotide on immune response in mice - Reidel, Ivana Gabriela (2017)
The development of novel vaccines requires the design of new adjuvants able to give long lasting immune responses. Our aim was to obtain cationic liposomes as adjuvants by an industry-suitable method, and evaluate them using bovine serum albumin (BSA) as immunogen and CpG oligonucleotides with phosphodiesther bonds, as immunostimulants. Liposomes (Lip) were prepared with dipalmitoylphosphatidylcholine, cholesterol and stearylamine by Ethanol Injection method. Immune response was assessed by immunization of Balb/c mice with: Lip+BSA Lip+BSA+CpG, CpG+BSA or aluminium hydroxide (Al(OH)3+BSA). Liposomal formulations were able to induce high antibody levels. Lip+BSA+CpG led to higher IgG levels than Lip+BSA (p<0.05, Mann-Whitney) and elicited the highest IgG2a levels. All the formulations induced antigen specific cellular proliferation, without significant differences, meanwhile Lip+BSA+CpG produced the highest levels of IFN-γ. These results showed these liposomes are versatile vehicles to potentiate and target the immune system to vaccination, leading to high humoral and cellular immune responses.